Pengaruh Media Induksi terhadap Multiplikasi Tunas dan Pertumbuhan Planlet Pisang Rajabulu (AAB) dan Pisang Tanduk (AAB) pada Berbagai Media Multiplikasi - Kasutjianingati , (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
The aim of this research was to study the effects of explant from various induction media on multiplication and growth of cv Rajabulu (AAB) and Tanduk (AAB) plantain. This research was arranged in factorial complete randomized design with two factors. The fi rst factor was two kinds of explant which came from induction media I1 (MS + BA 2 mg L-1 + IAA 3 mg L-1), and from induction media I2 (MS + BA 2 mg L-1 + IAA 3 mg L-1 + TDZ 0.09 mg L-1); the second factor was 4 kinds of multiplication media, i.e. MS0 (control/without PGR), MS + BA 0.20 mg L-1 + IAA 0.01 mg L-1 (M1), MS + BA 1 mg L -1 + IAA 0.25 mg L-1 (M2), MS + BA 2 mg L-1 + IAA 0.5 mg L-1 (M3). The experiment results were the use of TDZ in the induction medium reduced the use of high cytokinin in the multiplication level. The use of Rajabulu explant that came from media I2 produced more shoots (4.3 shoots per explan) compared to explant from media I1 (3.2 shoots per explan). The use of multiplication media M3 and M2 produced the highest shoot number. The best shoot morphogenesis produced when the shoots after subculture in media with PGR (M3 or M2) to media MS0 (big shoot 3.1 and medium shoot 3.5). Tanduk plantain’s shoot was responsive to cytokinin. The best treatment is I1-M3 with the highest number of shoots and the highest percentage of big and medium shoot is (33%) compared to other treatments (<17 %). In the second subculture, the highest shoot number were obtained from multiplication media M3 and M2. The morphogenesis of Tanduk plantain produced the highest big shoot if subcultured to media M3-M0 and M2-M0, followed to M0-M0. Keywords: TDZ, cytokinin, auxin, morphogenesis, big shoot, medium shoot